IMPROVEMENT OF THE PRODUCT AND QUALITY OF POGOSTEMON CABLIN BENTH - Allwar Allwar; is fatimah; noor fitri; dwiarso rubiyanto (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2014)
Pogostemon cablin benth is an economic source of farmer communities which are presence in several provinces in Indonesia. In general, the production and quality of the Pogostemon cablin benth produced by the farmers are still low or under the standard ISO. The chelating method, the influence of pH and adsorption method with activated carbon and montmorilonite were carried out to improve the production and quality of Pogostemon cablin benth. The results show that the production and the quality tends to be better proved by the color changes to yellow bright, reduced metal contents and an increase in Pogostemon cablin benth